A Systemic Functional Linguistic Analysis of Mood Structures in News Coverage of Anies Baswedan’s Speech During Presidential Election Debates in The Jakarta Post and TEMPO.CO - Haritsyah, Yevis; Sawirman, Sawirman; Zulprianto, Zulprianto (Universitas Mataram, 2024)
The purpose of this study is to use Halliday’s Systemic Functional Linguistics viewpoint to uncover the interpersonal meanings that are realized in five selected news articles from The Jakarta Post and TEMPO.CO. This study employed a qualitative method. The data source is two articles from The Jakarta Post and three articles from TEMPO.CO, all under the categories of the 2024 presidential election debate. The data were collected through textual analysis and close reading techniques. The results of this research are as follows: (1) The declarative mood is frequently used across all five articles with 97% for TJP and 99% for TC. The sentences are mostly realized by temporal deicticity, while modality appears in small percentages. (2) Both TJP and TC potray Anies Baswedan positively but with different emphases. TJP highlights Baswedan’s personal attributes and political background. TC emphasizes Baswedan’s political expertise and policy proposals. This distinction in focus reflects the different strategies employed by TJP and TC to shape public perception during the election period. TJP and TC employ similar tenor patterns where they position themselves as equals to their readers and conveying a positive tone in their interactions.